Study on Oxidation Resistance Effect of Catechin Esters - Qiang, Lin; Qing, Huo (Asian Journal of Chemistry, 2012)
Catechins were enzymatically esterified with stearic acid by an immobilized lipase Novozym435 in organic solvent (n-butanol) at 60 ºC. The reaction time is ca. 96 h. Through extraction by column chromatography, the purified catechin esters were collected. The antioxidative activity of catechin esters and catechin had been studied by peroxide value, hydroxyl radicals's clearance and superoxide radical clearance. Peroxide value of catechin esters was the lowest before 48 h, Catechin esters showed better antioxidative activity than the standard antioxidant BHT and other species. The esters had stronger scavenging effect for ˆOH and O2-ˆ than catechin. So catechin esters can be used as an antioxidant to alleviate the additive oxidation process.